Influence of nanocomposite preparation techniques on the multifunctional properties of carbon fabric‐reinforced polystyrene‐based composites with carbon nanotubes. (11th July 2022) - Erkmen, Berrak; Bayram, Goknur
Abstract: Polystyrene (PS)‐based and carbon fabric‐reinforced polymers (CFRPs) containing elastomer were prepared using the compression molding technique. PS was also reinforced with two types of carbon nanotubes (CNTs), as received and modified with a silane‐coupling agent. Nanocomposites were fabricated with two different methods, masterbatch dilution, and direct melt mixing. The effect of the nanocomposite preparation technique on the mechanical properties, electrical resistivity, and shape memory behavior of the multilayer composites was investigated. The tensile strength and tensile modulus of the multilayer composite containing CNTs modified with silane coupling agent, and prepared with masterbatch dilution method, increased by 33% and 34%, respectively, compared with the composites prepared with melt mixing. With the masterbatch dilution technique, the electrical resistivity was lower, and slightly increased with surface modification of CNTs. In both preparation techniques, the possible combined effect of CNTs and CF on the thermal and electrical conductivity of the composites led to 100% shape recovery lower than 30 s with electrically actuated bending test. Abstract : Preparation of Polystyrene Nanocomposites with Masterbatch Dilution and Direct Melt Mixing Techniques, and Their Use and Assessment for the Carbon Fabric‐Reinforced Polymers.